2020
DOI: 10.1002/app.49401
|View full text |Cite|
|
Sign up to set email alerts
|

A correlation between morphology and mechanical performance of injected‐molded PE/EVA/clay nanocomposites: Insight into phase miscibility and interfacial phenomena

Abstract: In this study, the correlations between the mechanical performance and structural properties of injected‐molded polyethylene (PE)/ethylene‐vinyl acetate copolymer (EVA)/nanoclay (NC) nanocomposites are investigated by revisiting the interfacial phenomena and miscibility state of the component pairs. The effects of different parameters including the injection molding temperature, mixing sequence in melt‐compounding process, blend composition, and nanoclay loading are studied. A great complexity arises in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The cross-linked hybrid structure with some regular pores in Figures 8f and 9d dramatically enhanced the phonon scattering. In addition, the uniform distribution of the anisotropic orientation of h-BN flakes had the pinning effect and further promoted the improvement of thermal stability and mechanical reliability [44,45]. Therefore, the synergetic effect of the POB and h-BN multi-component fillers improved the comprehensive properties of PTFE-based composites.…”
Section: Thermal Stability Of Ptfe-based Composites With Multi-component Fillersmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross-linked hybrid structure with some regular pores in Figures 8f and 9d dramatically enhanced the phonon scattering. In addition, the uniform distribution of the anisotropic orientation of h-BN flakes had the pinning effect and further promoted the improvement of thermal stability and mechanical reliability [44,45]. Therefore, the synergetic effect of the POB and h-BN multi-component fillers improved the comprehensive properties of PTFE-based composites.…”
Section: Thermal Stability Of Ptfe-based Composites With Multi-component Fillersmentioning
confidence: 99%
“…The composite with 25 wt.% POB and 5 wt.% h-BN showed a cross-linked structure with regularly distributed pores, which was further conducive to higher thermal stability and thermal conductivity (see Figure 8f and Table 3). In addition, the h-BN as the second phase possessed the pinning effect of phase boundaries, which enhanced the mechanical properties [43,44]. SEM images of the fracture surface for PTFE composites filled with different h-BN contents are shown in Figure 9.…”
Section: Effect Of Morphology and Molecular Structure On The Thermal-mechanical Propertiesmentioning
confidence: 99%
“…[6][7][8][9][10] However, the properties of these liner material pose critical challenges for enhancing the hydrogen storage density and properties of the aforementioned tanks, including the barrier properties (for HDPE) and mechanical properties as well as machinability (for PA6 as well). 8,[11][12][13] Previous work [14][15][16][17][18] have indicated that the free-volume and permeability path of liner materials are the key factors that affect their gas barrier properties. Thus, effective measures 13,[19][20][21][22] to improve the barrier properties involve employing functional fillers with highbarrier properties or optimizing the aggregation structure.…”
Section: Introductionmentioning
confidence: 99%
“…8,[11][12][13] Previous work [14][15][16][17][18] have indicated that the free-volume and permeability path of liner materials are the key factors that affect their gas barrier properties. Thus, effective measures 13,[19][20][21][22] to improve the barrier properties involve employing functional fillers with highbarrier properties or optimizing the aggregation structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation